The Impact of Sex and Biological Maturation on Physical Fitness in Adolescent Badminton Players - Jaime Fernandez-Fernandez; Alba Herrero-Molleda; Francisco Álvarez-Dacal; Jose Luis Hernandez-Davó; Urs Granacher (MDPI AG, 2023)
The main objective of this study was to examine the impact of maturity status and sex on selected measures of physical fitness in adolescent badminton players. Eighty-one badminton players (39 boys, 42 girls; age: 12.7 ± 1.4 years; body height: 153.5 ± 10.5 cm; body mass: 48.3 ± 13.2 kg) participated in the study and were divided into pre-peak height velocity (PHV, n = 31), circa-PHV (n = 29), and post-PHV (n = 21) groups. The assessment of physical fitness included linear sprint (5-m, 10-m) and change-of-direction (CoD) speed tests using a modified 5-0-5 CoD test (CoD deficit [CoDD%]) and an on-court CoD test, as well as the countermovement jump (CMJ) test as a proxy of lower limbs' muscle power. Pre-PHV players presented lower performance levels (p < 0.001; ES: 1.81-1.21) than post-PHV in CMJ, linear sprint (5, 10-m) speed, and both CoD tests. In addition, compared to circa-PHV, pre-PHV players demonstrated moderately lower performances in the 10 m sprint and CoD tests (p < 0.05; ES: 0.65-1.00). Regarding the CoDD%, no between-group differences were found. Irrespective of the maturity status, boys outperformed girls in CMJ (p = 0.01; ES: 0.71), linear sprint speed (p < 0.05, ES: 0.52-0.77), and the modified 505 test (p = 0.01; ES: 0.71). Findings only showed significant sex-by-maturity interactions for the pre-PHV group. In addition, sex-related performance differences were found in favor of the boys for most measures except for CoDD%. Our results imply that maturity status (i.e., PHV) and not chronological age should be used to design training programs. Female adolescent badminton players should receive specifically targeted exercise interventions based on their fitness status and needs.